Exploring Early-Career Job Seekers' Online Uncertainty Management. (April 2023) - Smith, Stephanie A.; Piercy, Cameron; Zhu, Yaguang
Using the framework of uncertainty management theory (UMT), this study qualitatively explores the extent to which entry-level job seekers engage in online information seeking, or cybervetting, about employers, why they do it, and how cybervetting influences their subsequent communication. We conducted 19 focus groups, involving 100 participants across three universities, to capture the rich experiences of early-career job seekers. Findings offer evidence of cybervetting from the perspective of a potential employee, exploring how information-seeking foregrounds the modern employee-employer relationship. The findings indicate that many job seekers use social media and employee-generated review websites as an initial mode of communication to find organizational information that helps to manage their uncertainty and anxiety, prepare for interviews, engage with their existing interpersonal networks because of information they find online, and to aid in their decision-making about joining organizations. In line with UMT, many participants also use cognitive and behavioral alternatives to information seeking to manage their uncertainty.